1980
DOI: 10.1002/pol.1980.180180517
|View full text |Cite
|
Sign up to set email alerts
|

Oriented cellulose films and fibers from a mesophase system

Abstract: SynopsisCellulose mesophases were obtained by preparing concentrated solutions of cellulose (20-5570) in a mixture of N-methyl-morpholine N-oxide (MMNO) and water. The anisotropy depends on four interconnected parameters: the temperature of the solution which, in general, must be lower than 90°C; the concentration of cellulose which must exceed 20%; a water content such that the mole ratio water/anhydrous MMNO is smaller than unity; and the degree of polymerization of the dissolved cellulose. The anisotropic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
72
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(73 citation statements)
references
References 8 publications
1
72
0
Order By: Relevance
“…Basically NOC was prepared by stretching a water-swollen cellulose film that had been coagulated from a dimethylacetamide͞LiCl solution. Dissolution of cellulose and preparation of the template was accomplished by a previously described procedure (4) using a solvent exchange technique (12). Strips Ϸ30 mm long and 5 mm This paper was submitted directly (Track II) to the PNAS office.…”
Section: Methodsmentioning
confidence: 99%
“…Basically NOC was prepared by stretching a water-swollen cellulose film that had been coagulated from a dimethylacetamide͞LiCl solution. Dissolution of cellulose and preparation of the template was accomplished by a previously described procedure (4) using a solvent exchange technique (12). Strips Ϸ30 mm long and 5 mm This paper was submitted directly (Track II) to the PNAS office.…”
Section: Methodsmentioning
confidence: 99%
“…8 The cellulose solutions in anhydrous NMMO crystallize at lOO'C, producing a cellulated structure. 8 Chanzy et al 9 and Navard and Haudin 15 observed a phase transition from anisotropic to isotropic takes place at the range from 88 to 90'C from the rheological measurement of cellulose (DPw 900) solutions in NMMO hydrates with n, range from 0.3 to 0.54, which hydrates were prepared by simple mixing of anhydrous NMMO and water. Referring to our result for NMMO hydrates with n, range from 0.45 to 0.65 the secondary and the third crystallization takes place in the range from 80 to 120'C.…”
mentioning
confidence: 99%
“…But solvents were very limited in metal complexes, strong acids and salts, due to highly developed intra-and intermolecular hydrogen bonds in cellulose solid. 1 For these thirty years, new organic and inorganic solvents, such as N,N-dimethylacetamide (DMAc)jlithium chloride (LiC1) 2 • 3 and amine oxide containing water, 4 liquid ammonia/ammonia thiocyanate, 5 • 6 and aqueous (aq) sodium hydroxide (NaOHf- 9 have been found and the dissolving mechanisms of cellulose into these solvents have been intensively investigated. For some solvents, the solubility of cellulose is exclusively governed by the structure of cellulose solid.…”
mentioning
confidence: 99%